TANGGUNG JAWAB PEMELIHARAAN DAN NAFKAH ANAK-ANAK DALAM HAL KEDUA ORANG TUANYA BERCERAI DI KALANGAN WARGA NEGARA INDONESIA YANG BERAGAMA HINDU - S U M E N S U M E N (PREMISE LAW JURNAL, 2015)
Divorce is not recognized in Hinduism, but in practice often resulting in divorce child maintenance purposes. In the result, in case of divorce then pemeliaharaan children are often in the hands of his mother without the imposition of allowance of the child's natural father. Maintenance of children due to divorce their parents according to the Law No. 1 of 1974 was in the hands of both parents even if the child is under the care of the maintenance ibunya.Hambatan children whose parents are divorced according to Hinduism economic factors, factors parents remarried, psychological factors, parental factors women are able to provide cost a living child. While efforts to address the maintenance of children whose parents divorced according to the teachings of Hinduism is to increase the role and responsibilities of parents who divorced over religious institutions such as the existence of the Hindu Association of Indonesia (PHDI) and increasing the role and responsibilities of the community and the state for the maintenance of children of divorce parents who are not able to do the maintenance of the child. Keywords: Maintenance, Child, Parents, Divorced, Hindu Religion